Comprehensive analysis of bacteriocins in Streptococcus mutans - Atsuko Watanabe (Nature Portfolio, 2021)
Abstract Streptococcus mutans produces bacteriocins that show antibacterial activity against several bacteria. However, comprehensive analysis of these bacteriocins has not been well done. In this study, we isolated 125 S. mutans strains from volunteers and determined their whole genome sequence. Based on the genome analysis, the distribution of each bacteriocin gene (mutacins I-IV, K8 and Smb) was investigated. We found 17, 5, and 2 strains showing 100% matches with mutacin I, mutacin II and mutacin III, respectively. Five mutacin III-positive strains had 2 mismatches compared to mature mutacin III. In 67 mutacin IV-positive strains, 38 strains showed 100% match with mutacin IV, while 29 strains showed some variations. In 23 mutacin K8- and 32 mutacin Smb-positive strains, all except one mutacin K8-positive strain showed 100% match with the mature peptides. Among 125 strains, 84 (65.1%), 26 (20.2%), and 5 (3.9%) strains were positive for one, two and three bacteriocin genes, respectively. Then, the antibacterial activity against oral streptococci and other oral bacterial species was investigated by using bacteriocin gene single-positive strains. Each bacteriocin gene-positive strain showed a different pattern of antibacterial activity. These results speculate that individual S. mutans strains may affect the bacterial composition of dental plaques.